A computerized mathemetical approach to menu planning - Gürdal, Hakan. (Thesis (M.S.)- Bogazici University. Institute for Graduate Studies in Science and Engineering, 1986., 1986)
In this thesis it is aimed to develop monthly or bimonthly menu planning methodologies for institutions serving three meals per day. The menus generated are to satisfy certain nutritional, structural and variety requirements at least possible cost. For the purposes stated above multistage and single stage linear and integer programming models are developed and solved using B.U. CDC-Cyber computer and TUBITAK VAX-7BO computer. Data for these models (Dish selections and their nutrient contents, human nutritional requirements etc.) have been obtained from Nutrition and Food Technology Division of TUBITAK. In order to include subjective evaluations of decision maker and food system manager and nonquantifiable factors (such as taste and suitability) interactive modules are added to the developed system.
Keywords: Quantity cookery.; Menus.; Food service.